Comparison of One-Stage Managements in the Treatment of Obstructing Left-Sided Colorectal Cancer: Endolaparoscopic Approach vs. Emergency Open Surgery - Yingdong CHENG; Hua YANG; Zhicao ZHANG; Guoqing CHEN; Guangsheng DU; Dan MA (Tehran University of Medical Sciences, 2015)
Letter to the Editor